Study of genus Origanum L. in conditions of Southern coast of Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The results of investigation of biomorfological and economically valuable characteristics of six species of genus Origanum L. in conditions of a Southern coast of Crimea are summed up. High-productive forms have been recommended to cultivation in the south of Ukraine and apply in food industry and in medicine.
Keywords: Origanum L., essential oil, phenology, essential glands, sort sample.